Social control of homosexual gay behavior Among adolescents in pontianak city - Daniel, Daniel; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to analyze the nature, process, outcomes, obstacles, and mitigation of social control over homosexual gay behavior among adolescents in Pontianak City. Using a qualitative approach with a case study method, data were collected through in-depth interviews with two gay adolescents, participatory observation, and documentation of policies and media reports. The data were analyzed through reduction, presentation, and verification using source and time triangulation. The findings indicate that social control in Pontianak is still dominated by preventive approaches, which are not yet effectively integrated and are mostly limited to reproductive health education by specific institutions. Curative approaches through community-based rehabilitation also face constraints related to limited resources and high levels of social stigma. Persuasive control is primarily carried out by families and communities through methods such as reprimands, moral advice, and religious approaches, which often result in psychological pressure for adolescents. The main barriers to effective social control include the absence of specific regulations, weak coordination among agencies, and resistance from both the public and the LGBT community. Proposed mitigation strategies include strengthening the role of families as primary supervisors, fostering collaboration among schools, communities, formal institutions, and law enforcement, with an emphasis on educational and humanistic approaches. Community-based rehabilitation models that have proven effective in other countries are recommended for adaptation, alongside religious and traditional moral value-based approaches to strengthen adolescents"™ character and awareness. In conclusion, social control of homosexual gay behavior in Pontianak City requires a more inclusive, consistent, and structured multisectoral synergy that addresses the psychosocial and emotional aspects of adolescence in order to foster a supportive and harmonious environment for the moral development of the younger generation in line with local social and cultural norms.